The Experience of Non-Full-Time Nursing Graduate Students in China: A Qualitative Study - Ou, Na; Qi, Sanyang; Hu, Minmin; Hu, Jimei; Tang, Sanyuan (International Journal of Public Health and Medical Research, 2024)
To address the disconnection between the educational structure of nursing teams and the rapid development of China's medical and health industry, there is a shortage of highly educated nursing personnel. In 2016, Chinese universities introduced a new training model for nursing graduate students: non-full-time nursing graduate students. Due to its late development, this model needs continuous improvement. Understanding the training experience of non-full-time nursing graduate students is crucial for refining the training model. This study explores the experiences of non-full-time nursing graduate students and provides a basis for improving their training in China. Semi-structured qualitative interviews were conducted with 20 non-full-time nursing graduate students. Data were collated and analyzed using Colaizzi's method. The analysis identified five themes related to the study experiences of non-full-time nursing graduate students: (1) maladaptation to diversified roles; (2) weak scientific research foundation; (3) lack of high-level guidance in clinical practice; (4) concern about social recognition; and (5) lack of educational and training resources. Competent government and training units should fully understand the experiences of non-full-time nursing graduate students and improve their training model from the students' perspective to promote the development of high-quality nursing talents. This will ultimately benefit employers, training units, individuals, and patients.